2021
DOI: 10.1111/ijfs.14946
|View full text |Cite
|
Sign up to set email alerts
|

Cooking does not impair the impact of pulsed electric field on the protein digestion of venison (Cervus elaphus) during in vitro gastrointestinal digestion

Abstract: Summary The present study was conducted to elucidate whether cooking impairs the positive effect of pulsed electric field (PEF) on the digestibility of venison during in vitro gastrointestinal protein digestion. Previous studies have used fresh uncooked meat to demonstrate the effect of PEF on protein digestibility during gastrointestinal digestion neglecting the effect that cooking could induce during meat preparation process. PEF‐treated samples (T1, 10 kV, 90 Hz, 20 µs) were cooked (core temperature of 75 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…All these processes have the potential to affect the bioavailability and quality of the proteins present in meat and meat products. Emerging technologies, such as PEF (Bhat et al, 2020a;Bhat, Morton, Mason, & Bekhit, 2019c, 2018dBhat, Morton, Mason, Bekhit, & Mungure, 2019), and non-thermal processes, such as curing and ripening (Bhat et al, 2021a), have been reported to affect the digestibility of muscle proteins. The impact of both emerging technologies and non-thermal processes on the digestibility of muscle proteins have been reviewed recently (Bhat et al, 2021a, b).…”
Section: Meat Processing and Muscle Protein Digestibilitymentioning
confidence: 99%
“…All these processes have the potential to affect the bioavailability and quality of the proteins present in meat and meat products. Emerging technologies, such as PEF (Bhat et al, 2020a;Bhat, Morton, Mason, & Bekhit, 2019c, 2018dBhat, Morton, Mason, Bekhit, & Mungure, 2019), and non-thermal processes, such as curing and ripening (Bhat et al, 2021a), have been reported to affect the digestibility of muscle proteins. The impact of both emerging technologies and non-thermal processes on the digestibility of muscle proteins have been reviewed recently (Bhat et al, 2021a, b).…”
Section: Meat Processing and Muscle Protein Digestibilitymentioning
confidence: 99%
“…PEF processing of whole egg white or isolated egg white proteins (e.g., lysozyme and ovalbumin; Perez & Pilosof, 2004;Zhao & Yang, 2008) has resulted in the exposure of buried SH and hydrophobic groups/regions and even induced the cleavage of S-S bonds (e.g., in lysozyme), consequently leading to protein aggregation (Liu et al, 2018;Wu, Zhao, Yang, et al, 2014;Zhao & Yang, 2012). Recently, PEF has been reported to increase the digestibility of food proteins such as beef, venison, milk, and egg proteins Bhat, Morton, Mason, Jayawardena, et al, 2019;Bhat, Morton, Mason, Jayawardena, et al, 2020;Liu et al, 2018Liu et al, , 2017. Although the structural changes induced by PEF processing have been widely studied in egg proteins, only a few studies have reported the impact of PEF on the digestibility of egg proteins and needs scientific attention.…”
Section: Pulsed Electric Fieldmentioning
confidence: 99%
“…Furthermore, during salting, Na + and Cl − disrupt the hydration layer on the protein's surface, providing more binding sites for pepsin and improving digestibility [8]. Pulsed electric field processing might also improve the digestibility of meat proteins by inducing structural and microstructural changes in the protein and increasing access to meat protein hydrolysis sites [9]. It is reported that VPS treatment improved the in vitro digestibility of roasted duck protein compared to roasted ducks after SWS, indicating that VPS treatment promoted protein degradation [10].…”
Section: Introductionmentioning
confidence: 99%